Abstractive Text Summarization Berita Bahasa Indonesia Menggunakan Retrieval-Augmented Generation - Antonius Sakti Wiradinata; Viny Christanti Mawardi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
This research discusses the application of Abstractive Text Summarization (ATS) to Indonesian language news using the Retrieval-Augmented Generation (RAG) method. Increased access to news through various digital platforms often causes users to have difficulty identifying relevant information among the large amount of news available. RAG integrates retrieval and generation techniques to produce coherent and informative news summaries. In this research, news from the CNN and CNBC sites was collected via web scraping to form a dataset. The data is processed through several stages, including preprocessing, embedding, information retrieval, and summary generation. Summary quality evaluation was carried out using the ROUGE metric, where the test results show that this system has good performance in the precision aspect, with a ROUGE-1 Precision value of 0.7432 and ROUGE-2 Precision of 0.6174. However, a lower ROUGE Recall value indicates that there is important information that is not fully included in the summary. These results indicate that the RAG method in ATS is effective in helping users obtain core information concisely, but there needs to be improvement in capturing the entire news context